Microscale Heat Transfer - Fundamentals and Applications Proceedings of the NATO Advanced Study Institute on Microscale Heat Transfer - Fundamentals and Applications in Biological and Microelectromechanical Systems, Cesme-Izmir, Turkey, 18-30 July, 2004 - Kakaç, S.; Vasiliev, L.L.; Bayazitoglu, Y.; Yener, Y.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2005)
This volume contains an archival record of the NATO Advanced Institute on Microscale Heat Transfer – Fundamental and Applications in Biological and Microelectromechanical Systems held in Çesme – Izmir, Turkey, July 18–30, 2004. The ASIs are intended to be high-level teaching activity in scientific and technical areas of current concern. In this volume, the reader may find interesting chapters and various Microscale Heat Transfer Fundamental and Applications. The growing use of electronics, in both military and civilian applications has led to the widespread recognition for need of thermal packaging and management. The use of higher densities and frequencies in microelectronic circuits for computers are increasing day by day. They require effective cooling due to heat generated that is to be dissipated from a relatively low surface area. Hence, the development of efficient cooling techniques for integrated circuit chips is one of the important contemporary applications of Microscale Heat Transfer which has received much attention for cooling of high power electronics and applications in biomechanical and aerospace industries. Microelectromechanical systems are subject of increasing active research in a widening field of discipline. These topics and others are the main themeof this Institute.
Single-Phase Forced Convection in Microchannels -- Measurements of Single-Phase Pressure Drop and Heat Transfer Coefficient in Micro and Minichannels -- Steady State and Periodic Heat Transfer in Micro Conduits -- Flow Regimes in Microchannel Single-Phase Gaseous Fluid Flow -- Microscale Heat Transfer at Low Temperatures -- Convective Heat Transfer for Single-Phase Gases in Microchannel Slip Flow: Analytical Solutions -- Microscale Heat Transfer Utilizing Microscale and Nanoscale Phenomena -- Microfluidics in Lab-on-a-Chip: Models, Simulations and Experiments -- Transient Flow and Thermal Analysis in Microfluidics -- From Nano to Micro to Macro Scales in Boiling -- Flow Boiling in Minichannels -- Heat Removal Using Narrow Channels, Sprays and Microjets -- Boiling Heat Transfer in Minichannels -- Condensation Flow Mechanisms, Pressure Drop and Heat Transfer in Microchannels -- Heat Transfer Characteristics of Silicon Film Irradiated by Pico to Femtosecond Lasers -- Microscale Evaporation Heat Transfer -- Ultra — Thin Film Evaporation (UTF) — Application to Emerging Technologies in Cooling of Microelectronics -- Binary-Fluid Heat and Mass Transfer in Microchannel Geometries for Miniaturized Thermally Activated Absorption Heat Pumps -- Heterogeneous Crystallization of Amorphous Silicon Accelerated by External Force Field: Molecular Dynamics Study -- Hierarchical Modeling of Thermal Transport from Nano-to-Macroscales -- Evaporative Heat Transfer on Horizontal Porous Tube -- Micro and Miniature Heat Pipes -- Role of Microscale Heat Transfer in Understanding Flow Boiling Heat Transfer and Its Enhancement -- Heat Transfer Issues in Cryogenic Catheters -- Sorption Heat Pipe — A New Device for Thermal Control and Active Cooling -- Thermal Management of Harsh-Environment Electronics -- Thermal Transport Phenomenon in Micro Film Heated by Laser Heat Source.
Keywords: Energy systems; Chemical engineering; Energy Systems; Industrial Chemistry/Chemical Engineering